The ecology of trust among hackers. - Dupont, Benoît; Côté, Anne-Marie; Savine, Claire; Décary-Hétu, David (Global Crime, 2016)
Malicious hackers profit from the division of labour among highly skilled associates. However, duplicity and betrayal form an intrinsic part of their daily operations. This article examines how a community of hackers uses an automated reputation system to enhance trust among its members. We analyse 449,478 feedbacks collected over 27 months that rate the trustworthiness of 29,985 individuals belonging to the largest computer hacking forum. Only a tiny fraction of the forum membership (2.4%) participates in the vast majority (75%) of ‘trust exchanges’, limiting its utility. We observe a reporting bias where the propensity to report positive outcomes is 2.81 times greater among beginner hackers than among forum administrators. Reputation systems do not protect against trust decay caused here by the rapid expansion of the community. Finally, a qualitative analysis of 25,000 randomly selected feedbacks indicates that a diverse set of behaviours, skills and attitudes trigger assessments of trustworthiness.